THE ROLE OF MALE AND FEMALE PRINCIPALS OF PUBLIC SCHOOLS IN PROVIDING HEALTH SERVICES TO SCHOOLS OF JERASH – JORDAN - Omar, Khitam Ahmed Bani (European Scientific Journal, ESJ, 2013)
This study aimed to identify the degree of male and female principals of public schools in providing health services to schools of Jerash. The study sample consisted of (63) male and female principals of Jerash schools– Jordan. To achieve the goal of the study, the researcher presented a questionnaire which was checked of sincerity and persistence. After making an appropriate statistical analysis, the results showed the following: The degree of male and female principals of public schools in providing health services to schools of Jerash was medium as a whole. The results also showed that arithmetic mean of paragraphs related to the role of male and female directors of public schools in providing health services ranged from (2.12 to 4.85), where (29) paragraphs were significantly with high degree of such practice, and (20) paragraphs came moderately, and (10) paragraphs were with a low degree of practice. In light of the findings above, the study recommended a series of recommendations including: providing adequate financial allocations for schools to provide health needs as well as paying much attention to water taps, toilets and washrooms in schools that need to be with a high quality and with sufficient numbers.